GENE-08. THE MNP 2.0 STUDY: PROSPECTIVE INTEGRATION OF DNA METHYLATION PROFILING IN CNS TUMOR DIAGNOSTICS. (23rd April 2019) - Sturm, Dominik; Sahm, Felix; Andreiuolo, Felipe; Rode, Agata; Grund, Kerstin; Hirsch, Steffen; Rutkowski, Stefan; Bison, Brigitte; Gessi, Marco; Warmuth-Metz, Monika; von Deimling, Andreas; Pietsch, Torsten; et al.
Abstract: There is a broad variety of CNS tumor entities that can affect children and adolescents, associated with divergent clinical outcomes. We have recently proposed a DNA methylation-based classification to distinguish biologically distinct CNS tumor classes within and across neuropathological entities. The Molecular Neuropathology 2.0 study integrates genome-wide (epi-)genetic diagnostics with reference neuropathological assessment for newly-diagnosed pediatric CNS tumors in Germany. From 04/2015 to 09/2017, 607 patients with sufficient tissue were enrolled from 51 German centers. A reference neuropathological diagnosis according to the WHO classification was established for 95% of tumors and reflected the distribution of known histological CNS tumor entities in a pediatric population. Using 10 FFPE sections for DNA extraction, a DNA methylation-based molecular diagnosis was established in 95% of cases, of which 83% were assigned to a distinct CNS tumor methylation class. The remaining 17% did not match any of 82 currently established classes, but revealed evidence for novel rare molecular entities. Gene panel sequencing of >130 genes performed for 88% of patients with matched blood samples indicated diagnostically, prognostically, or therapeutically relevant somatic alterations in 47%. Germline DNA sequencing indicated potential predisposition syndromes in 10% of patients, leading to human genetic counselling of affected families. Discrepant results by neuropathological and (epi-)genetic classification ( 20%) were discussed in a weekly multi-disciplinary tumor board including reference neuroradiological evaluation. The majority of clinically-relevant discrepancies (67%) involved tumors neuropathologically diagnosed as high-grade gliomas, of which 25% were showed discrepant results. Clinical follow-up of enrolled patients through the German HIT study centers is ongoing. The MNP 2.0 study adds a valuable layer of information to clinical neuropathological diagnostics and has expanded to an international registry for molecular data analysis for pediatric CNS tumors. The results provide insight into tumors with divergent neuropathological and molecular classification with potential implications for patient management.